The influence of personality traits on teachers’ communication styles - Ahmed, Nasrulla; Md Sidek, Suzana Suhailawaty; Lawsha, Mohamed; Abdulla, Asifa (Valley International Journal, 2024)
Teachers' traits have a significant influence on their teaching perspectives, pupil retention, and satisfaction, while constant and effective communication is critical to improving the excellence of educational institutions (Dhillon & Kaur, 2023; James H. Stronge, 2018). Teachers' communication styles, which are influenced by their fundamental personality traits, have a direct impact on overall educational quality(Ahmed & Naqvi, 2015). Research has demonstrated that a teacher's personality may be an effective instrument for creating a good and productive learning environment (Ahmed & Naqvi, 2015; Dhillon & Kaur, 2023). The current study examined the influence of personality traits on teachers’ communication styles. Teachers' ideas, feelings, and credibility, molded by personality traits, are critical to their ability to transmit information and promote an effective learning environment (Buttner et al., 2015; Renta Davids et al., 2017). According to Costa et al. (1995) personality is permanent patterns of thinking, feeling, and behaving that identify individuals, and it plays an important role in how educators interact with their students and approach education